Applications of Chitosan Polymer Membrane to Removal Methyl Orange Dye from Aqueous Solutions: Aplikasi Membran Polimer Kitosan untuk Menghilangkan Pewarna Metil Oranye dari Larutan Berair - Sammah Naeem Ghazi; Saleh Abdel-Sahib Shamukh; Abbas Essam Abdulhassan; Ali JassimEbadi; Muhammad Youssef Jarmal; Rana Ali Qanbul; Rehab Saad abd Ali; Fatima abdalzahra laibi; Fatima Mohammed Mahdi; Zahraa Ali Hussein; Zahraa Mohammed Hassan (Academia Open, 2024)
In this study, membranes made from chitosan, a natural polymer derived from shrimp shells, were investigated for their ability to remove toxic methyl orange (MO) dye from water. The membranes were characterized using infrared spectroscopy, and the maximum absorption wavelength of MO dye was determined via UV-Visible spectrophotometry. Solutions of varying MO concentrations were passed through the chitosan membranes, and their absorbance was measured before and after filtration. Results showed high removal rates ranging from 85% to 95%, with the highest efficiency observed at 20 ppm MO concentration. This research highlights the potential of chitosan membranes as effective and sustainable solutions for water purification, addressing a crucial environmental and health concern posed by toxic dye pollution. Highlights: High removal rates: Chitosan membranes remove dye efficiently (85%-95%). Eco-friendly: Derived from shrimp shells, chitosan offers sustainable water purification. Advanced analysis: Infrared spectroscopy and UV-Visible spectrophotometry characterize membrane properties. Keywords: Chitosan membranes, Water pollution, Methyl orange dye, Removal efficiency, Environmental sustainability